Evaluation of Pre-Departure English Training Program - Ali Saukah (Universitas Negeri Malang, 2016)
The program evaluation reported in this article covers three batches of participants, from 1996 through 1997, sponsored by the Directorate General of Higher Education projects to prepare faculty members of teacher training institutions for overseas studies. The result outcomes could be achieved when the initial English competence requirred for participating in the program was at least at the Pre-Advanced level. The criterion validity of the TOEFL-Equivalent test developed by the program was assured, and the test could, therefore, be used as a good predictor of the International TOEFL. Other recommendations are also given for the improvement of the planning and implementation of the program in the future